Gastronomic Tourism in Central Java: Examining The Antecedents of Tourist Revisit Intention - Dwi Amini; Sulis Riptiono; Harini Abrilia Setyawati; Intan Muliana Rhamdhani (School of Business, Bogor Agricultural University (SB-IPB), 2025)
Background: Gastronomic tourism is gaining traction and is recognized as a strategic dimension of destination marketing in the digital age. Therefore, examining the factors that shape tourists' revisit intentions is crucial for researchers and destination managers.Purpose: This study examines how influencer marketing reviews shape revisit intentions by incorporating social media engagement, influencer trust, and gastronomic experiences within an empirical model framework.Methodology: This quantitative study involved 440 tourists who had experienced gastronomic tourism in Central Java. Data were collected through questionnaires administered to visitors during their trips, employing a convenience sampling approach, and subsequently analyzed using SEM-AMOS.Finding: The results indicate that influencer marketing reviews play an important role in increasing social media engagement, trust, and intention to revisit but are not significant for gastronomic experience. In addition, gastronomic experience and trust in influencers are proven to be significant for the intention to revisit, while social media engagement is not significant. Gastronomic experience has the greatest influence on increasing repeat visits by tourists to gastronomic tourism.Conclusion: Tourist intention to revisit gastronomic tourism can increase owing to the influence of influencer marketing reviews, trust in influencers, and gastronomic experience. Additionally, reviews from influencers are significant for social media engagement and trust in influencers.Originality/value (state of the art): This research provides knowledge and adds insight into the intention to revisit Gastronomic Tourism, especially in Central Java. Keywords: gastronomic experience, influencer, social media, revisit intention, heritage